Ex-haciendas tourism in Puebla-Tlaxcala and its relationship to processes of regional development - Ríos Elorza Serafín; Guevara Romero María Lourdes (Revista Mexicana de Ciencias Agrícolas, 2018)
Patrimonial potential, represented by the ex-Hacienda in Puebla and Tlaxcala, is in eminent danger of disappearing, since, of 434 ex-haciendas registered in Puebla, 25% are only in good conditions, according to Yanes and Ríos (2014). It is important to understand the economic consequences that this represents, in addition to the loss of opportunity that would mean for the waste of productive potential in the ex-Hacienda. It is intended to analyse in the study area, the capacities of local agents of tourism, as the infrastructure resources, attractions and services as well, for the pursuit of strategies of bonding rural tourism of former farms to local and regional development, from a scheme of productive reconversion and touristic diversification. The investigation period was from 2012 to 2014, the method and methodology used was mainly qualitative, using various interpretive techniques that describe, translate and synthesize the meaning of the facts. The main results in the ex-hacienda of Amoltepec, Zacatlán, Puebla, show that a suitable model of productive reconversion and the ex-haciendas tourism diversification, bonding rural tourism of ex-haciendas to local and regional development processes, supported by skills and local resources, make viable to generate income opportunities for the surrounding communities.